Microstructural evaluation by confocal and electron microscopy in thrombi developed in central venous catheters - Lucas,Thabata Coaglio (2017)
Abstract OBJECTIVE Evaluating thrombi microstructure developed in central venous catheters using confocal and electron microscopy. METHOD An experimental, descriptive study carrying out a microstructural evaluation of venous thrombi developed in central venous catheters using Scanning Electron Microscopy and Confocal Laser Scanning Microscopy. RESULTS A total of 78 venous catheters were collected over a period of three months. Different fibrin structures were distinguished: fibrin plates, fibrin network, and fibrin fibers. It was observed that the thrombus had thick fibrin plates adhered to the catheter wall openings in both a catheter with three days of permanence as well as in a catheter with 20 days of insertion in the patient. However, a greater amount of erythrocytes and fibrin fibers were found in the central region of the thrombus. CONCLUSION This study contributes to improving health care and can have a positive impact on clinical practice, as easy adherence of platelets and fibrins to the catheter wall demonstrated in this study makes it possible to adopt thrombus prevention strategies such as therapy discontinuation for an extended period, blood reflux by a catheter, slow infusion rate and hypercoagulo pathyclinical conditions.